Effectiveness of the attachment position in molar intrusion with clear aligners: a finite element study - Dian Fan; Hao Liu; Chang-Yong Yuan; Shi-Yu Wang; Peng-Lai Wang (BMC, 2022)
Abstract Objective To evaluate the biomechanical effects of different attachments' position for maxillary molar intrusion with clear aligner treatment by finite element analysis. Methods Cone-beam computed tomography images of a patient with supra-eruption of the maxillary second molars were selected to construct three-dimensional models of the maxilla, periodontal ligaments, dentition, and clear aligner. The models were divided into four groups depending on the attachment location on the first molar: (1) no attachment (NA), (2) buccal attachment (BA), (3) palatal attachment (PA), and (4) bucco-palatal attachment (BPA). After applying an intrusion of 0.2 mm on the second molar, displacements and stress distributions of the teeth, aligner, and periodontal ligament were analyzed with the finite element software. Results All groups displayed equivalent movement patterns of aligners. The NA and BA groups showed buccal tipping of the second molar, while the PA group showed palatal tipping. The BPA group had the highest intruding value and the lowest buccal/palatal tipping value. All groups showed mesial tipping of the second molar. Stress distribution in the periodontal ligament strongly correlated with the attachment position. The BPA group showed the best stress distribution. Conclusion Combined BA and PA could effectively prevent buccal and palatal tipping and showed the best efficiency in intruding the second molar. The second molar showed an unavoidable tendency to tip mesially, regardless of the attachment position.